Comparison of spleen transcriptomes of two wild rodent species reveals differences in the immune response against Borrelia afzelii. Issue 13 (25th May 2020) - Zhong, Xiuqin; Lundberg, Max; Råberg, Lars
Abstract: Different host species often differ considerably in susceptibility to a given pathogen, but the causes of such differences are rarely known. The natural hosts of the tick‐transmitted bacterium Borrelia afzelii, which is one of causative agents of Lyme borreliosis in humans, include a variety of small mammals like voles and mice. Previous studies have shown that B. afzelii‐ infected bank voles ( Myodes glareolus ) have about ten times higher bacterial load than infected yellow‐necked mice ( Apodemus flavicollis ), indicating that these two species differ in resistance. In this study, we compared the immune response to B. afzelii infection in these host species by using RNA sequencing to quantify gene expression in spleen. Gene set enrichment analysis (GSEA) showed that several immune pathways were down‐regulated in infected animals in both bank voles and yellow‐necked mice. Moreover, IFNα response was up‐regulated in B. afzelii ‐infected yellow‐necked mice, while IL6 signaling and the complement pathway were down‐regulated in infected bank voles; differences in regulation of these three pathways between bank voles and yellow‐necked mice could thus contribute to the difference in resistance to B. afzelii between the species. This study provides knowledge of gene expression induced by a zoonotic pathogen in its natural host, and possible species‐specific regulation of immune responses associated with resistance. Abstract : Previous studies have shown that Borrelia afzelii ‐infected bank voles have about ten times higher bacterial load than infected yellow‐necked mice, indicating that these two species differ in resistance. In this study, gene set enrichment analysis (GSEA) showed that IFNα response was up‐regulated in B. afzelii ‐infected yellow‐necked mice, while IL6 signaling and the complement pathway were down‐regulated in infected bank voles; differences in regulation of these three pathways between bank voles and yellow‐necked mice could thus contribute to the difference in resistance to B. afzelii between the species.